Memoir: The founding of PIDS - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2017)
The Philippine Institute for Development Studies (PIDS), founded in 1977, has gained international recognition for useful research on development issues relevant to the nation's economic needs. In this memoir prepared for the 40th anniversary celebration of the institute's birth, the author recounts the unique circumstances, philosophy and other factors that led to the founding of the research institute.
Keywords: A11; O21; O29; O53; 330; Philippine economy; economic development; research institutions